TEACHING OF PHYSICS IN GENERAL SECONDARY SCHOOLS - Muhammadova Dilafruz Akhmatovna; Fayzieva Kholida Asadovna (American Journals Publishing, 2023)
This article aims to achieve effective results in a short period of time in modern education as opposed to traditional education. In this case, in the teaching of physics, the volume of lesson hours is quantitatively measured in accordance with the student's ability to know. For this purpose, the use of innovative technologies, the improvement of the quality of physics classes in secondary schools, the increase of students' interest in the lesson, the formation of creative research and independent work, and the formation of cooperative work skills are discussed.
Keywords: non-traditional lesson, innovative technology, motivation, cognitive activity, management activity, exhibition tools.